Isolation and Antagonist Test of Lactic Acid Bacteria from Fermented Kepok Banana against Escherichia coli - Salsabilla, Kharisma Namira; Trimulyono, Guntur (LenteraBio : Berkala Ilmiah Biologi, 2022)
Escherichia coli is one of the patogenic bacteria that can cause digestive infection if the number exceeds normal limits in the human intestine. This infection can be prevented by utilizing probiotic bacteria. One of the probiotic groups is lactic acid bacteria (LAB). Sources of LAB can be obtained from fermented foods. This study aimed to isolate LAB from fermented kepok banana sample and to test the antagonistic activity of LAB isolates in inhibiting the growth of E. coli. The method of isolation is pour plate. LAB character test was carried out macroscopically by observing colony and cell morphology as well as microscopically including Gram staining, endospore staining, catalase test, and motility test. The antagonist test was carried out using the well diffusion method. Antagonist test data were analyzed using the Kruskal Wallis test with post hoc Bonferroni test. The isolation results showed that five LAB isolates were coded BTPK1, BTPK2, BTPK3, BTPK4, and BTPK5. The results showed that the average inhibition zone of LAB against E. coli ranged from 4.33-6.00 mm. The five LAB isolates from fermented kepok banana sample obtained had the ability to inhibit the growth of E. coli.